Same-day discharge following transcatheter aortic valve replacement: a propensity-matched analysis from national readmission database. (3rd October 2022) - Goel, A; Malik, A; Bandyopadhyay, D; Chakraborty, S; Gupta, R; Hajra, A; Abbott, J D; Ahmad, H
Abstract: Background: The length of hospital stay following transcatheter aortic valve replacement (TAVR) has decreased in recent years, and next-day discharge strategy is being increasingly adopted in some centers. Whether it is safe to further expedite discharge post-TAVR in selected patients by allowing discharge on the same day as the procedure remains unknown. In addition to potentially decreasing hospitalization costs, it could also limit the inpatient footprint and strain on healthcare resources. Purpose: The purpose of our study was to compare the 30-day readmission rate in patients receiving TAVR who were discharged the same day (same-day discharge or SDD group) with those who were discharged on a different day (different-day discharge or DDD group). Additionally, we aimed to identify risk factors for readmission after TAVR. Methods: We used the United States Nationwide Readmission Database to identify all adults who underwent elective TAVR in the years 2015–2019. The primary outcome of this study was all-cause 30-day readmission rate. The secondary outcomes were total hospital costs for the index admission, and risk factors for 30-day readmission. Propensity score matching was conducted to compare the SDD and DDD groups. Independent risk factors of 30-day readmission were identified using multivariate Cox proportional hazards regression analysis of the unmatched cohort. Results: Of the 196, 618 patients who received TAVR (mean age 79.5±8.4 years, 45.0% females), 245 (0.12%) patients were discharged on the same day they received TAVR (SDD group), and the remaining 196, 373 were discharged on a different day (DDD group). In the DDD group, the median length of hospital stay was 2 days (interquartile range 1–4 days). A 1:3 propensity score analysis generated a matched cohort including 245 and 889 patients in the SDD and DDD groups, respectively. The 30-day readmission rate was similar between the SDD and DDD groups (11.0% versus 10.8%, hazard ratio [HR] 1.01, 95% confidence interval [CI] 0.59–1.71, p=0.989). Hospitalization costs were significantly lower in the SDD group than the DDD group (37, 811±18, 029 versus 49, 130±27, 007, p<0.001) (see Picture 1). Age, female gender, history of diabetes, chronic kidney disease, chronic pulmonary disease, oxygen use, prior stroke, peripheral vascular disease, anemia, liver disease, and cancer were found to be independent risk factors for 30-day readmission after TAVR (see Picture 2). Conclusion: In this large nationwide database analysis, patients receiving uncomplicated TAVR who were discharged on the same day as the procedure had a similar all-cause 30-day readmission rate and significantly lower hospital costs compared to those discharged on a different day. These results indicate that same-day discharge after TAVR may be a safe and feasible option in carefully selected patients. Funding Acknowledgement: Type of funding sources: None.